FACTOR ANALYSIS – GROWTH, SIZE, PROFITABILITY, LIQUIDITY FACTORS ON BOND RATING - Risawati, Risawati (International Journal of Social and Management Studies, 2020)
This study analyzes the factors that can influence the prediction of bond ratings on companies listed on the Indonesia Stock Exchange using accounting factors, namely company growth (Growth) as measured by the book to market ratio, company size (Size) as measured using total assets, profitability as measured using return on investment (ROA) and liquidity as measured using current assets (Current Ratio). In taking or determining the sample, taken in a targeted manner, as many as 36 series of bonds can be obtained from companies listed on the Indonesia Stock Exchange which are rated by PT Pefindo in 2017 to 2019. The data used are secondary data, data obtained and collected from documents- documents owned by the company. In this study, the variables that have a significant effect on the rating are Growth, Size, while the profitability and liquidity variables do not have a significant effect on bond ratings.